Level of Knowledge of the Diabetic Patient about the Prevention of Diabetic Foot. - Georgina Jiménez Estrada; María Teresa Martínez Barroso; Marta Gómez Arcila; Hilda Carmouce Cairo (Medisur)
Background: The education of the diabetic patient is a fundamental factor for the diabetes mellitus, even in its condition of chronic disease, it will not reach major complications. Objective: To analyze the level of knowledge about the prevention of diabetic food in patients who are carriers of diabetes mellitus. Method: A descriptive study was carried out in 5 family doctor´s offices belonging to the IV area of Cienfuegos Municipality, in a period of time among February and April 2006. The sample was formed by 68 diabetic patients to whom a survey was applied. Results: A high per cent (86.4) of our patients knew about some of the complications related to this disease. At evaluating the level of knowledge, an acceptable average was found. Conclusions: The level of knowledge in the surveyed patients was not enough. The treatment of these patients should also include these kinds of informations considering the complications the patients can suffer from.